The Effect of Using a Skillful and Recreational Physical Exercise in Some of the Motor Abilities of Middle School Students in Physical Education Lesson - Abdullah Rajab, Shaymaa; Mohammed Saeed, Sundus (International Journal of Psychosocial Rehabilitation, 2020)
The research problem manifested itself through a physical education lesson that has been subjected to a lot of neglect due to the reduction of its systematic classes and making it one share given to students between one week and another, which in turn was reflected in the students’ deterioration of physical fitness and its delay in this physical aspect and the reflection of its image from the psychological point of view in the lack of motivation of students to practice activities Sports and their demand for the lesson, as we find its clear effects on the behavior of students during the lesson and their lack of interaction with it, and the research sample was chosen intentionally, which is the fifth stage. Students from Al-Mughaira Bin Shuba School in Ramadi for the academic year 2018-2019, and they are (40) students, (20) for the control group and (20) for the trial, have been selected for the applicability of the research. The research sample (40 students) was chosen in a random, irregular way (the lottery), with a rate of 20 students for each group, and the experimental groups outperformed the control group because of the vocabulary prepared from exercises and their use in a new method contributed to achieving the objectives of the lesson through the implementation of students’ motor duties They have increased their focus on exercises and games in the study unit with systematic freedom, as this freedom has a major impact on developing the student’s personality through reliance on himself without external pressure, which leads to increased enthusiasm and excitement during performance.